The impact mechanism of intensive English programs on the well-being of Chinese EFL learners in Malaysia: Using the PERMA model - Liu, Sibo; Mohd Rashid Bin Mohd Saad (Journal of International Students, 2025)
This study explores the impact of intensive English programs on the well-being of Chinese EFL learners in Malaysia, using the PERMA model as a framework. The research employs a qualitative case study approach, focusing on learners from Hebei Province to examine how Positive Emotions, Engagement, Relationships, Meaning, and Accomplishment contribute to their overall well-being. Through thematic analysis of participant experiences, the study highlights how interactive activities, peer support, and milestone achievements foster emotional resilience, motivation, and academic success. Emerging themes, such as cultural adaptation strategies and perseverance, extend the PERMA model to a cross-cultural context, emphasizing the interplay between language learning and psychological growth. The findings have practical implications for designing culturally responsive and emotionally supportive intensive English programs. They underscore the importance of integrating positive psychology principles into curriculum design and providing tailored support systems for learners in cross-border educational settings.